The Adamello-Presanella Group (Rhaetian Alps): a key site for understanding recent glaciers variations - BARONI, CARLO; SALVATORE, MARIA CRISTINA; Carton A. (Comitato Glaciologico Italiano, 2014)
The Alps are a sensitive environment towards the ongoing climate changes, to which they are reacting with variations in the extension of glaciers and permafrost and with an increasing in the frequency and magnitude of mass-wasting processes. The Alps have been referred in the Mountain Agenda as the “water tank of Europe” representing the source area of many important rivers. To focus the glaciers behaviour as response to recent global changes we investigated more than one hundred glaciers of the Adamello-Presanella Group. Present day glaciers of the this group, including the widest glacier of Italian Alps the Ghiacciaio dell’Adamello, extend for more than 50 km2. We reconstruct LIA glacial limits through geomorphologic and glacial geologic field surveys; areal variations occurred in the 20th and 21th Centuries have been inferred from historical maps and multitemporal aerial photographs. Since the Little Ice Age (LIA), whose climax was reached in the Alps around 1850 AD, alpine glaciers experienced a period of manifest reduction, with a strong reduction in thickness and areal extension, broken by very few brief and weak advances. More than 140 glaciers developed during the LIA covered an area almost the double of their present surface. The elevation of the Equilibrium Line Altitude (ELA), areal and volume variations underline a strong reduction since the LIA. The notable frontal regression is marked by withdrawals ranging from several hundred meters to more than 2000 m. Considering the maximum LIA and 1983 AD glaciers extension of the Presanella Group, they lost about 55% of the total area while the mean value for the entire Adamello– Presanella Group is about 50%. An additional reduction of about 25% occurred between 1983 and 1999 AD. More recently, several glaciers of the group remained below the annual snowline and show dramatic areal and volumetric reductions.